2010
DOI: 10.1038/ismej.2010.171
|View full text |Cite
|
Sign up to set email alerts
|

Examining the global distribution of dominant archaeal populations in soil

Abstract: Archaea, primarily Crenarchaeota, are common in soil; however, the structure of soil archaeal communities and the factors regulating their diversity and abundance remain poorly understood. Here, we used barcoded pyrosequencing to comprehensively survey archaeal and bacterial communities in 146 soils, representing a multitude of soil and ecosystem types from across the globe. Relative archaeal abundance, the percentage of all 16S rRNA gene sequences recovered that were archaeal, averaged 2% across all soils and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
672
11
20

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,115 publications
(772 citation statements)
references
References 54 publications
43
672
11
20
Order By: Relevance
“…DNA concentrations for each amplification reaction were measured with the Nanodrop 2000 (Thermo Scientific, Bremen, Germany) and B600 ng of DNA from each reaction was pooled, then sent to the Ramaciotti Centre for Gene Function Analysis for sequencing using the GS-FLX pyrosequencing platform (Roche, Mannheim, Germany). For 16S rRNA amplicon sequencing, original cave DNA (rather than Phi29-amplified DNA) was used as a template in PCR with the primer set F515 and R806 of Bates et al (2011), which have been shown to successfully amplify an B250 bp region of the 16S rRNA gene from both bacteria and archaea (Bates et al, 2011). Reactions were performed in triplicate 25 ml reactions using the FastStart High Fidelity PCR System (Roche) according to the manufacturer's instructions with 1 ml template DNA.…”
Section: Methodsmentioning
confidence: 99%
“…DNA concentrations for each amplification reaction were measured with the Nanodrop 2000 (Thermo Scientific, Bremen, Germany) and B600 ng of DNA from each reaction was pooled, then sent to the Ramaciotti Centre for Gene Function Analysis for sequencing using the GS-FLX pyrosequencing platform (Roche, Mannheim, Germany). For 16S rRNA amplicon sequencing, original cave DNA (rather than Phi29-amplified DNA) was used as a template in PCR with the primer set F515 and R806 of Bates et al (2011), which have been shown to successfully amplify an B250 bp region of the 16S rRNA gene from both bacteria and archaea (Bates et al, 2011). Reactions were performed in triplicate 25 ml reactions using the FastStart High Fidelity PCR System (Roche) according to the manufacturer's instructions with 1 ml template DNA.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was amplified in triplicate using primers specific to either the 16S or 18S rRNA gene. A portion of the 16S rRNA gene was amplified using the Archaea-and Bacteriaspecific primer set 515f/806r [20]. This 16S primer set is designed to amplify the V4 -V5 region of both Archaea and Bacteria, has few biases against specific taxa and accurately represents phylogenetic and taxonomic assignment of sequences [25].…”
Section: (C) Central Park Community-level Sequence Analysismentioning
confidence: 99%
“…We quantified the diversity living within the soils via high-throughput sequencing of a hypervariable region of the 16S small subunit rRNA gene for the bacterial and archaeal analyses [20] and a comparable region of the 18S rRNA gene for the eukaryotic analyses. For reasons of consistency and for lack of a better definition that applies across all three domains [14,21], we define a phylotype as those taxa that share greater than or equal to 97% sequence similarity in the targeted rRNA gene regions, following convention [22].…”
Section: Introductionmentioning
confidence: 99%
“…This notion was subsequently challenged by culture-independent diversity surveys that documented the occurrence of the Archaea in both extreme Orphan et al, 2000;Benlloch et al, 2001Benlloch et al, , 2002Baker and Banfield, 2003) and temperate habitats, for example, soil (Bintrim et al, 1997;Walsh et al, 2005;Bates et al, 2011;Tripathi et al, 2013), marine environments (DeLong, 1992;Fuhrman et al, 1992;Massana et al, 1997;Karner et al, 2001) and freshwater ecosystems (Lin et al, 2012;Yergeau et al, 2012;Berdjeb et al, 2013;Bricheux et al, 2013;Silveira et al, 2013;Vila-Costa et al, 2013). In addition to establishing the ubiquity of the Archaea on a global scale, these studies have also significantly expanded the scope of phylogenetic diversity within this domain, as many of the sequences identified represented novel, high-rank phylogenetic lineages (DeLong, 1992;Vetriani et al, 1999;Takai et al, 2001;Hallam et al, 2004;Elkins et al, 2008;Hu et al, 2011;Nunoura et al, 2011).…”
Section: Introductionmentioning
confidence: 99%